Developing a thinking skills assessment tool to evaluate students in institutions of higher learning / Parmjit Singh … [et al.] - Singh, Parmjit; Thambusamy, Roslind; Mahmud, Zamalia; Abdullah, Imran Ho (Research Management Institute (RMI), 2013)
This study is premised on the contention that there is a lack of appropriate screening methods and tools to ensure the quality of graduating university students which is ironic considering the intensity of the screening mechanisms in place select and sanction entry to the university. Other than academic achievements, no other forms of formal screening are practiced and thus, in due course, results in the massification of undesirable fresh graduates with low employability capabilities flooding the job market. At the outset, it must be established that the unemployment concern has long been haunting Malaysian fresh graduates in spite the fact that it is no longer something new to the Malaysian context. By the wake of 2006, for example, 20,217 unemployed graduates registered with the Malaysian Ministry of Human Resources' Career Assistance Program to aid them find suitable employment. (Ministry of Human Resources, 2009). Even as recent as late 2011, 40,000 graduates remain jobless, having to resort to part time, freelance, and odd jobs to sustain their living conditions (Bernama, Education Transformation Needful, 2012). The predicament is clear and neither the government nor the employers are holding back the truth: many of the graduates are simply unwanted. The usage of the word unwanted is most appropriate here, as the lack of job opportunities is not the primary reason for such a disturbing trend of unemployment. The origin of the problem seems to point to the graduates themselves…